Factors influencing the perception Felda's young generation toward working in plantation industry / Abdul Halim Roslam Razali - Roslam Razali, Abdul Halim (Faculty of Plantation and Agrotechnology, 2015)
In order to face the problem lack of local workers in the plantation fields, the industry must find ways to overcome this problem by attract the Malaysian citizen to participate in the industry. Felda's young generation is the potential people that can contribute in the industry because they are used to lie in the plantation environment along their life. Then a survey has been conducted based on the factor influencing perception of Felda's young generation toward working in the plantation industry. There are several factors that have significant correlate with the perception of young generation. Therefore, the industry need to think about the factors relating to the participation by the young generation. Then the objective of this research is to identify the main factors affecting the perception of Felda's young generation toward working in the plantation industry and then to identify their interest to involved in the industry. Other, than that, this research aimed to discover which variables in the main perception that are most dominant and had strong correlation between the variable. This study was conducted in Felda Keratong 1, Pahang. On this study, the analysis method use to analyse the data was the correlation and multiple regressions analysis. In addition, the information that provided in this study hopefully can help the industry to overcome the influx of foreign workers in the plantation by exchange to labour from the local people.